Economic Growth and Poverty Reduction in Sub-Saharan Africa - Moser, Gary (IMF Working Papers; Working Paper, 2001)
This study confirms a strong and robust relationship between economic growth and poverty reduction in sub-Saharan Africa. Employing a panel of 46 countries covering the period 1972-97, the analysis finds that a 10 percent increase in per capita GDP leads to a 1 percent increase in life expectancy, a 3-4 percent decline in infant mortality rates, and a 3 1\2 -4 percent increase in the rate of gross primary school enrollment. The results are robust for high- and low-income, as well as fast- and slow-growth, countries. The study also finds that quality of growth, civil conflict, HIV/AIDs, civil and institutional freedom, and island economies are important control variables that help explain the variability of poverty across Africa. A country's latitude is not found to be a significant factor explaining life expectancy or infant mortality rates, though it is a significant factor explaining gross primary school enrollments.